2014
DOI: 10.1002/bjs.9496
|View full text |Cite
|
Sign up to set email alerts
|

Blood clearance of Howell–Jolly bodies in an experimental autogenic splenic implant model

Abstract: Splenectomy has been practised routinely, both in the emergency setting and as a therapeutic elective procedure. There is a correlation between asplenia/hyposplenia and the occurrence of fulminant sepsis, underlining the importance of developing surgical methods for preserving splenic function. Both clinical and experimental studies have shown at least partial morphological and functional regeneration of autogenic splenic implants (ASIs). Experimental studies investigating the immunoprotective effect of ASIs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This was based on data provided by Charles River Laboratories International (Wilmington, MA, USA) as being the mean hematocrit for 8 –10‐week‐old Lewis male and female rats using samples from animals housed in their standard production setting . Wright–Giemsa‐stained blood smears were prepared for all samples and examined microscopically for abnormal RBC morphology such as target cells, RBC fragments, and RBC corpuscular inclusions such as Howell–Jolly bodies as indicators of splenic dysfunction . Smears were also examined for WBC morphology and WBC precursors, and a manual differential WBC count was performed ( n = 100 cells per smear) to confirm the automated differential WBC count results.…”
Section: Methodsmentioning
confidence: 99%
“…This was based on data provided by Charles River Laboratories International (Wilmington, MA, USA) as being the mean hematocrit for 8 –10‐week‐old Lewis male and female rats using samples from animals housed in their standard production setting . Wright–Giemsa‐stained blood smears were prepared for all samples and examined microscopically for abnormal RBC morphology such as target cells, RBC fragments, and RBC corpuscular inclusions such as Howell–Jolly bodies as indicators of splenic dysfunction . Smears were also examined for WBC morphology and WBC precursors, and a manual differential WBC count was performed ( n = 100 cells per smear) to confirm the automated differential WBC count results.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that without residual spleen, Howell-Jolly bodies persist indefinitely. 19 In a study in male Wistar rats, Howell-Jolly bodies were no longer identified on blood smear when 22.5% of spleen mass was present. 19 Both mTESp and hTESp contained CD4-and CD11cpositive cells that also indicated donor origin with either lamin or GFP costaining.…”
Section: Discussionmentioning
confidence: 99%
“…19 In a study in male Wistar rats, Howell-Jolly bodies were no longer identified on blood smear when 22.5% of spleen mass was present. 19 Both mTESp and hTESp contained CD4-and CD11cpositive cells that also indicated donor origin with either lamin or GFP costaining. Although there are multiple cell types of myeloid and lymphoid lineage required for the function of innate and adaptive immunity, both T cells and dendritic cells are required for spleen function.…”
Section: Discussionmentioning
confidence: 99%
“…When the spleen is absent or insufficient, the number of HJB containing erythrocytes is increased (29). In the present study, the mice in the depression model group exhibited higher counts of HJB, which indicated that splenic function was compromised.…”
Section: Discussionmentioning
confidence: 99%